Cumhuriyet dönemi din eğitimine genel bir bakış: . Atatürk'ün İslam dini ve din eğitimi hakkındaki görüşleri - Ayhan, Halis (Marmara Üniversitesi İlahiyat Fakültesi Dergisi, 2000)
Ataturk's opinions about religion extremely affected changes and developments in the field of religious education in the formative period of Republic. Ataturk wanted all educatlanal institutions, including religious on es, to be bo und to the control of Ministıy of Education. According to him eveıybody living in Turkey had to Iearn one's religion in schools. "There is not a clergy in Islam, so eveıy Muslim should take religious knowledge at schools (in equal conditioils). Therefore. in Republic Period, all organic educational institutions -from primaıy !eve! to higher edtication- was tried to be reconstructed. These efforts were regarded necessaıy for a reconstruction of individual and social life. In fact, when the religious education and instruction is examined from the histarical point of view, a continuity is not be discerned. Posltive points of Ottoman and Seljuk educational experience were not added to the Republic education, furthermore our educational experience in Republic period could not be used to a desired extent, especially in the field of religious education.